Genre et migrations - Nadia Ouabdelmoumen (Glad!)
Drawing on a research that questioned the reproduction of gender and power relations in the implementation of the language related components of the Accommodation and Integration Contract (CAI) in Rennes, this paper looks into the interpretation of « autonomy » as a principle revealing normative logics and situated social relations, that are delimited by the application process of this apparatus of French immigration policies. At a time when individualised and contractualised monitoring processes have been increasingly used to promote individualised autonomy/empowerment mechanisms, this fieldwork study, settled in a training organisation authorised to deliver the linguistic training of the CAI in Rennes, describes how these offered-required trainings reveal a form of injunction to autonomy, that is primarily directed at women trainees, through the practice of French. This thus illustrates how autonomy, as an ideal expected to challenge forms of social control, infuses the apparatus by making invisible the power relations that are inherent to it.